2016
DOI: 10.1007/s10741-016-9529-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological mechanism and therapeutic role of S100 proteins in cardiac failure: a systematic review

Abstract: S100 proteins are a family of highly acidic calcium-binding proteins involved in calcium handling in many tissues and organs. Some of these proteins are highly expressed in cardiac tissue, and an impairment of some specific S100 proteins has been related to heart failure. To check this hypothesis, we decided to review the literature since 2008 until May 2015. According to the studies collected, recovering S100A1 levels may enhance contractile/relaxing performance in heart failure, reverse negative force-freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…The latest advances in S100 proteins related to heart failure examined by Imbalzano et al . () reported that S100 proteins could be exploited as markers in stadiation and prognosis of chronic heart failure. Also, these proteins, especially S100a1, have emerged as an attractive therapeutic target in failing heart.…”
Section: Discussionmentioning
confidence: 99%
“…The latest advances in S100 proteins related to heart failure examined by Imbalzano et al . () reported that S100 proteins could be exploited as markers in stadiation and prognosis of chronic heart failure. Also, these proteins, especially S100a1, have emerged as an attractive therapeutic target in failing heart.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that S100A8/A9 can activate the vascular endothelium and increase endothelial permeability and has been found associated with atherogenesis and cardiovascular disease [37][38][39]. S100A8/A9 complex plasma levels were significantly higher in patients with chronic heart failure [40]. It is suggested that serum S100A8/A9 was shown to be associated with the severity of CAD in patients with diabetes mellitus [41,42].…”
Section: Fei Long Et Al Hub Genes In Coronary Artery Diseasementioning
confidence: 99%
“…SERCA2a activity can also be regulated by S100A1, which is a small protein highly expressed in the human heart. S100A1 influences Ca 2+ cycling through interacting with SERCA2a and PLN, RyR, as well as mitochondrial F1-ATPase activity 36. S100A1 can increase SERCA2a activity and thereby enhancing cardiac contractility 37.…”
Section: Serca2a Is a Target Of Interest For Treating Hfrefmentioning
confidence: 99%